Anarchy and Invention - World Bank (World Bank, Washington, DC, 2012)
Somalia has lacked a recognized government since 1991-an unusually long time. In extremely difficult conditions the private sector has demonstrated its much-vaunted capability to make do. To cope with the absence of the rule of law, private enterprises have been using foreign jurisdictions or institutions to help with some tasks, operating within networks of trust to strengthen property rights, and simplifying transactions until they require neither. Somalia's private sector experience suggests that it may be easier than is commonly thought for basic systems of finance and some infrastructure services to function where government is extremely weak or absent.